The Influence of Tourism Destination Components on Tourists’ Visit Intention from a Tourism Economics Perspective in Malioboro - Darini, Darini; Rachmawatie, Dessy; Ma'ruf, Ahmad (Dinasti Publisher, 2026)
Tourists’ visiting intention is an important indicator of destination sustainability and competitiveness. This study aims to analyze the effects of attraction, accessibility, amenities, and ancillary services on tourists’ visiting intention. A quantitative approach was employed using a survey method, in which primary data were collected through structured questionnaires distributed to tourists visiting the study destination. The data were analyzed using multiple linear regression, supported by partial significance testing (t-test) and simultaneous testing (F-test). The results indicate that all independent variables have a positive and statistically significant effect on tourists’ visiting intention. Among these variables, amenities show the strongest influence, followed by accessibility and ancillary services, while attraction has a significant but relatively weaker effect compared to the other variables. These findings suggest that tourists’ visiting intention is not solely driven by the attractiveness of the destination, but is largely determined by the quality of the experience perceived during the visit, particularly in terms of facility comfort and ease of access. Simultaneously, attraction, accessibility, amenities, and ancillary services are proven to have a significant combined effect on visiting intention, indicating that tourists’ decisions are shaped by the integrated interaction of multiple destination components. This study implies that destination development strategies should prioritize improvements in amenities and accessibility while maintaining the quality of attractions and ancillary services. The findings are expected to serve as a reference for destination managers and future researchers in developing tourism strategies that are oriented toward enhancing tourists’ experiences.